Data governance: Main challenges - Maria Savona (EconPol Forum, 2024)
Addressing the governance of emerging digital automation technologies and data in particular requires a multidisciplinary perspective, including techno-legal, geopolitical and economic expertise. Research on governing the process of individual and B2B data sharing, either through mandatory rules or the creation of incentives for sharing, will be important for setting the policy agenda. A "data-haven hypothesis" might explain asymmetries in the concentration of digital infrastructure, with countries with more stringent data protection, IP or tax regimes offshoring cloud services and data hubs to countries with weaker ones. The EU AI Act might lead to a new wave of the so-called "Brussels effect," even though it may still not be optimal and require further debate and public scrutiny.
Keywords: 330